2012
DOI: 10.4103/1947-2714.94940
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility patterns of urinary pathogens in female outpatients

Abstract: Background:Urinary tract Infection (UTI) is among the most common infections described in outpatient setting and hospital patients. In almost all cases empirical antimicrobial treatment initiates before the laboratory results of urine culture are available; thus antibiotic resistance may increase in uropathogens due to frequent use of antibiotics.Aims:The study was designed to find the prevalence of UTI in females with urinary tract symptoms, to determine the causative organism (s) of UTI, and to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(56 citation statements)
references
References 18 publications
9
45
0
2
Order By: Relevance
“…Current study observed high UTI in females of age group 13-40 years. This age group reported high risk for UTI cases and contribute highly sexually active women group (Dash et al, 2013;Nalini, Meenakshi, & Ramya, 2013;Shaifali, Gupta, Mahmood, & Ahmed, 2012). Nalini et al (2013) and Dash et al (2013) also presented the same results.…”
Section: Discussionsupporting
confidence: 71%
“…Current study observed high UTI in females of age group 13-40 years. This age group reported high risk for UTI cases and contribute highly sexually active women group (Dash et al, 2013;Nalini, Meenakshi, & Ramya, 2013;Shaifali, Gupta, Mahmood, & Ahmed, 2012). Nalini et al (2013) and Dash et al (2013) also presented the same results.…”
Section: Discussionsupporting
confidence: 71%
“…The present prevalence of UTI in pregnant women was lower than the prevalence figure reported from Ghana (29.9%) [24]. This variation may be explained by the differences in the environmental conditions, methodology adopted & characteristics of study populations such as social and food habits and the standard of personal hygiene [25]. The prevalence of bacteriuria among symptomatic and asymptomatic pregnant women was 20.4% and 17.8% respectively.…”
Section: Discussionmentioning
confidence: 72%
“…This might be due to the relatively poor hygienic practices in periurban and rural areas [41, 42] and geographical difference [25]. …”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with previous studies. [121923] Among sexually active young women the incidence of symptomatic UTI is high, and the risk is strongly associated with recent sexual intercourse, recent use of diaphragm with spermicide, and a history of recurrent UTIs. [24] Elderly males (≄68 years) had a higher incidence of CA-UTI (41.8%) when compared with the elderly females (10.3%).…”
Section: Discussionmentioning
confidence: 99%